EFFECT OF AGRO-PROCESSING, PRODUCTIVITY ENHANCEMENT, AND LIVELIHOOD IMPROVEMENT SUPPORT (APPEALS) PROGRAMME ON THE LIVELIHOOD OF FARMERS IN KOGI STATE, NIGERIA - Edoka, M. H.; Adiel, K. B.; Ojih, J. T. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was carried out in Kogi State, Nigeria. A total of 160 cashew farmers that participated in the programme were selected using a multi-stage random sampling procedure. A well-structured questionnaire was used in collecting data. Data collected were analyzed using descriptive statistics (frequencies, percentages and means) and inferential statistics (t-test and Tobit regression analysis). The results showed that majority (75.0%) of farmers were males with a mean age of 35.4 years. Majority (67.5%) were married having a mean household size of four persons, and 68.7% 68.7% of the farmers had farm sizes between 6-10 hectares, while the mean farm size and farming experience were 6.7 hectares and 22 years, respectively. Nearly half (46.3%) had secondary education, and 67.5% had extension contact, while 71.3% belonged to cooperative societies. The t-test results showed that, there was significant difference (P=<0.000) in yields and income of farmers before and after APPEALS programme participation. The results of Tobit regression revealed that income of farmers (P=0.039), friends and neighbours (P=0.065), and age (0.096) were statistically significant factors influencing farmers’ participation in APPEALS programme. Though, factors such as climate change (Mean= 3.3), limited extension contact (Mean= 3.1), and poor state of rural infrastructure (Mean= 3.0) hindered farmers from participating fully in the APPEALS programme. The study therefore recommended that; government should sustain this kind of programme to enable farmers improve in their farm operations, this can help them improve on cashew production. And farmers’ literacy should be given greater attention by government to enable them appreciate innovative ideas that can improve their farm productivity.